Malignant pleural mesothelioma: Germline variants in DNA repair genes may steer tailored treatment. (March 2022) - Sculco, Marika; La Vecchia, Marta; Aspesi, Anna; Pinton, Giulia; Clavenna, Michela G.; Casalone, Elisabetta; Allione, Alessandra; Grosso, Federica; Libener, Roberta; Muzio, Alberto; Rena, Ottavio; Baietto, Guido; et al.
Abstract: Introduction: Malignant pleural mesothelioma (MPM) is a tumour associated with asbestos exposure. Approximately, 10% of patients with MPM carry a germline pathogenic variant (PV), mostly in DNA repair genes, suggesting the occurrence of inherited predispositions. Aim: This article aimed to 1) search for new predisposing genes and assess the prevalence of PVs in DNA repair genes, by next-generation sequencing (NGS) analysis of germline DNA from 113 unselected patients with MPM and 2) evaluate whether these patients could be sensitive to tailored treatments. Methods: NGS was performed using a custom panel of 107 cancer-predisposing genes. To investigate the response to selected drugs in conditions of DNA repair insufficiency, we created a three-dimensional-MPM cell model that had a defect in ataxia telangiectasia mutated (ATM), the master regulator of DNA repair. Results: We identified PVs in approximately 7% of patients with MPM (8/113) and a new PV in BAP1 in a further patient with familial MPM. Most of these PVs were in genes involved or supposedly involved in DNA repair ( BRCA1, BRIP1, CHEK2, SLX4, FLCN  and BAP1 ). In vitro studies showed apoptosis induction in ATM-silenced/inhibited MPM spheroids treated with an enhancer of zeste homologue 2 inhibitor (tazemetostat). Conclusions: Overall these data suggest that patients with MPM and DNA repair insufficiency may benefit from this treatment, which induces synthetic lethality. Highlights: Germline pathogenic variants (PVs) are found in 7% of unselected patients with malignant pleural mesothelioma (MPM). Carriers of these PVs are more sensitive to asbestos than non-mutated patients. Most of these PVs occur in DNA repair genes that may be druggable. Tazemetostat targets MPM spheroids defective for DNA repair master gene ataxia telangiectasia mutated ( ATM ).